TACTICAL PREPARATION IN HANDBAL GAMES AT 13-15 YEARS - ROMILA C.; MACOVEI S. (Editura Universitatii Transilvania din Brasov, 2019)
Tactical training is a content element of sports training. Through tactical training the acquired technical procedures are highlighted. During the game their level of improvement is observed. Tactics tells us the purpose for which they have been used and why we need to use technical knowledge. As we want to improve the design, programming, implementation and applying the tactical handball training at the age of 13-15. We wish to know the opinion of teachers and coaches about the importance of tactical training at this age, we have carried out a questionnaire-based survey. The questionnaire was made on the website www.isondaje.ro. It was completed between 18th June 2018 - 25th July 2018. The questionnaire contains 16 questions with closed-ended answers. The people who answered our questionnaire were 112 coaches or teachers with handball specialization. The average age was 43 years. The analysis of the results was done by the statistical method, calculating the percentage for each response to the total sample. The findings of the study highlighted useful information on how tactical preparation is planned and implemented at the age of 13-15 years.